Thermal properties of Antarctic soils: wetting controls subsurface thermal state. Issue 5 (6th June 2016) - Levy, Joseph S.; Schmidt, Logan M.
Abstract: Mineral soils in the McMurdo Dry Valleys (MDV), Antarctica, are commonly considered to be dry, and therefore to be good insulators with low thermal diffusivity values (~0.2 mm 2 s -1 ). However, field measurements of soil moisture profiles with depth, coupled with observations of rapid ground ice melt, suggest that the thermal characteristics of MDV soils, and thus their resistance to thaw, may be spatially variable and strongly controlled by soil moisture content. The thermal conductivity, heat capacity and thermal diffusivity of 17 MDV soils were measured over a range of soil moisture conditions from dry to saturated. We found that thermal diffusivity varied by a factor of eight for these soils, despite the fact that they consist of members of only two soil groups. The thermal diffusivity of the soils increased in all cases with increasing soil moisture content, suggesting that permafrost and ground ice thaw in mineral soils may generate a positive thawing feedback in which wet soils conduct additional heat to depth, enhancing rates of permafrost thaw and thermokarst formation.